1981
DOI: 10.1007/bf00278697
|View full text |Cite
|
Sign up to set email alerts
|

Human inherited marker chromosome 22 short-arm enlargement: Investigation of rDNA gene multiplicity, Ag-band size, and acrocentric association

Abstract: The banding characteristics of an extreme variant familial chromosome 22 short-arm enlargement are described. Ag-AS staining for nucleolar-organizer regions, identified two areas of rDNA actively coding for 18S and 28S rRNA, the one being a broad distal Ag-band and the other a narrower centromeric Ag-band. The DNA in the major portion of the enlarged short arm was highly methylated, as shown by the binding of antibodies to 5-methylcytidine after UV-denaturation of chromosomal DNA. Mean Ag-band size on the aber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The relationship between Agstaining properties and the amount of rRNA gene copies is not exactly knowh until now. There are few investigations and they dealt with human chromosomes mainly (MILLER et al 1978;W ARBURTON and HENDERSON 1979;BERNSTEIN et al 1981;W ACHTLER et al 1986;DE CAPOA et al 1988;MKHITAROVA et al 1988). In the karyotype of the domestic horse (Equus caballus) NORs have been detected by silver staining (RICHER et al 1991) and FISH (MILLON et al 1993).…”
Section: Introductionmentioning
confidence: 97%
“…The relationship between Agstaining properties and the amount of rRNA gene copies is not exactly knowh until now. There are few investigations and they dealt with human chromosomes mainly (MILLER et al 1978;W ARBURTON and HENDERSON 1979;BERNSTEIN et al 1981;W ACHTLER et al 1986;DE CAPOA et al 1988;MKHITAROVA et al 1988). In the karyotype of the domestic horse (Equus caballus) NORs have been detected by silver staining (RICHER et al 1991) and FISH (MILLON et al 1993).…”
Section: Introductionmentioning
confidence: 97%
“…Prrez-Castillo et al (1986) detected up to four silver-stainable NORs in the DSR of a 15p+ variant found in four members of a sibship: in cells in which the DSR had only a single silver band, it was usually distal, and when two silver deposits were observed, they were over the distal and the proximal NOR. Finally, in a 22p+ marker chromosome found by Bernstein et al (1981) in four members of a family, three NORs were located in the DSR. Again, the largest silver signal was observed at the distal (near the telomere) NOR, followed by that of the proximal (near the centromere) NOR; the middle NOR showed transcriptional activity in only a few cells.…”
Section: Discussionmentioning
confidence: 98%
“…1985). Miller et al (1978) and Bernstein et al (1981) used both Ag-AS staining and in situ hybridization with a radioactive probe encoding ribosomal gene sequences to study two families: one with a 14p + and one with a 22p + These authors found that although the entire short arm was enriched in rRNA genes, as indicated by extensive hybridization in situ, the silver-impregnation sites were present only near the centromeric region and the distal end of the short arm in both families. It was concluded that the silver-impreg nation sites may only represent that portion of the genes that is transcriptionally active.…”
Section: Discussionmentioning
confidence: 99%